Cartoons as interdiscourse: A quali-quantitative analysis of social representations based on collective imagination in cartoons produced after the Charlie Hebdo attack. (March 2017) - Bouko, Catherine; Calabrese, Laura; De Clercq, Orphée
Abstract: The attacks against Charlie Hebdo in Paris at the beginning of the year 2015 urged many cartoonists – most professionals but some laymen as well – to create cartoons as a reaction to this tragedy. The main goal of this article is to show how traumatic events like this one can converge in a rather limited set of metaphors, ranging from easily recognizable topoi to rather vague interdiscourses that circulate in contemporary societies. To do so, we analyzed 450 cartoons that were produced as a reaction to the Charlie Hebdo attacks, and took a quali-quantitative approach that draws both on discourse analysis and semiotics. In this paper, we identified eight main themes and we analyzed the five ones which are anchored in collective imagination (the pen against the sword, the journalist as a modern hero, etc.). Then, we studied the cartoons at figurative, narrative and thematic levels thanks to Greimas' model of the semiotic square. This paper shows the ways in which these cartoons build upon a memory-based network of events from the recent past (particularly 9/11), and more generally on a collective imagination which can be linked to Western values. Highlights: We analyzed 450 cartoons by means of eight categories of motifs. We identified five types of interdiscourses based on collective imagination. Four of these five types consist of topoi.